2014
DOI: 10.1051/0004-6361/201220703
|View full text |Cite
|
Sign up to set email alerts
|

Two active states of the narrow-line gamma-ray-loud AGN GB 1310+487

Abstract: Context. Previously unremarkable, the extragalactic radio source GB 1310+487 showed a γ-ray flare on 2009 November 18, reaching a daily flux of ∼10 −6 photons cm −2 s −1 at energies E > 100 MeV and became one of the brightest GeV sources for about two weeks. Its optical spectrum shows strong forbidden-line emission while lacking broad permitted lines, which is not typical for a blazar. Instead, the spectrum resembles those of narrow emission-line galaxies. Aims. We investigate changes in the object's radio-to-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 174 publications
(194 reference statements)
0
10
0
Order By: Relevance
“…The SSRQ 4C+04.40 is part of a double association (with the FSRQ MG1 J120448+0408) of 3FGL J1205.4+0412. GB 1310+487 is a gamma-ray/radio-loud narrow-line AGN at z = 0.638, showing a gamma-ray flare in November 2009 and located behind the disk of an unrelated emission-line galaxy at z = 0.500 (Sokolovsky et al 2014).…”
Section: Non-blazar Objects and Misaligned Agnsmentioning
confidence: 99%
“…The SSRQ 4C+04.40 is part of a double association (with the FSRQ MG1 J120448+0408) of 3FGL J1205.4+0412. GB 1310+487 is a gamma-ray/radio-loud narrow-line AGN at z = 0.638, showing a gamma-ray flare in November 2009 and located behind the disk of an unrelated emission-line galaxy at z = 0.500 (Sokolovsky et al 2014).…”
Section: Non-blazar Objects and Misaligned Agnsmentioning
confidence: 99%
“…The development of VaST was mostly driven by the author's data processing needs. These evolved from a piggyback variability search in targeted CCD observations of known variable objects (Antipin et al 2005) to variability search using digitized photographic plates (Kolesnikova et al 2008, Sokolovsky et al 2014c), Swift/U-VOT data analysis (Sokolovsky 2009, Gupta et al 2012, visualization of CoRoT lightcurves (Sokolovsky et al 2010), photometry of individual active galactic nuclei (Schinzel et al 2011, Sokolovsky et al 2014d) and wide-field search for bright optical transients (Sokolovsky et al 2014b) that resulted in the discovery of Nova Sagittarii 2012 #1 (=V5589 Sgr; Korotkiy et al 2012. VaST was applied for variability search in CCD data by others including Majaess et al (2013), Lapukhin et al (2014), Kryachko et al (2015).…”
Section: Vast Applicationsmentioning
confidence: 99%
“…The observations of radio source GB 1310+487 by the FermiLarge Area Telescope (LAT; Atwood et al 2009) have shown the intense activity in the GeV γ-rays band and the twohumped structure in its spectral energy distribution (SED; Sokolovsky et al 2014), which are the typical features of blazars. Blazars are a peculiar class of active galactic nuclei (AGNs) having relativistic jets aligned close to the line of sight.…”
Section: Introductionmentioning
confidence: 99%
“…Three different states of GB 1310+487 were presented and preliminarily discussed by Sokolovsky et al (2014). ~´--in one day lasting about three weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation